Risk factors for postpartum depression in women undergoing elective cesarean section: A prospective cohort study - Lin, Rong; Lu, Yan; Luo, Wei; Zhang, Bing; Liu, Zhiqiang; Xu, Zhendong (Frontiers in Medicine, 2022)
Background: Postpartum depression (PPD) has adverse effects on maternal and child health. Cesarean section (CS) is suggested to be associated with PPD, but no study has examined the risk factors for PPD in women who underwent CS. Therefore, this study aimed to investigate this association. Methods: A prospective observational study was conducted between December 2020 and September 2021. In total, 590 women who underwent elective CS participated in this study. Data were collected using a questionnaire through a face-to-face interview at three time points: 32nd week of gestation, 2 days postpartum, and 6 weeks postpartum. PPD was defined by an Edinburgh Postnatal Depression Scale (EPDS) score of ≥11 at 6 weeks postpartum. Multivariate logistic regression analysis was performed to identify the risk factors for PPD. Results: Among the 590 women, 25.4% had PPD (142/590). After adjustment for the confounding factors, high antenatal self-rating anxiety scale score (OR=1.10, 95% CI=1.04–1.16), PPD symptoms (EPDS≥11) at 2 days postpartum (OR=6.17, 95% CI=1.35–28.31), and pain at 6 weeks postpartum (OR=2.14, 95% CI=1.24–3.69) were independently associated with PPD. Conclusions: Prenatal anxiety, PPD symptoms occurring at an early postoperative stage, and pain at 6 weeks postpartum may be associated with an increased risk of PPD among women who undergo CS.